In-plane deeply-etched optical MEMS notch filter with high-speed tunability. (15th October 2015) - Sabry, Yasser M; Eltagoury, Yomna M; Shebl, Ahmed; Soliman, Mostafa; Sadek, Mohamed; Khalil, Diaa
Abstract: Notch filters are used in spectroscopy, multi-photon microscopy, fluorescence instrumentation, optical sensors and other life science applications. One type of notch filter is based on a fiber-coupled Fabry–Pérot cavity, which is formed by a reflector (external mirror) facing a dielectric-coated end of an optical fiber. Tailoring this kind of optical filter for different applications is possible because the external mirror has fewer mechanical and optical constraints. In this paper we present optical modeling and implementation of a fiber-coupled Fabry–Pérot filter based on dielectric-coated optical fiber inserted into a micromachined fiber groove facing a metallized micromirror, which is driven by a high-speed MEMS actuator. The optical MEMS chip is fabricated using deep reactive ion etching (DRIE) technology on a silicon on insulator wafer, where the optical axis is parallel to the substrate (in-plane) and the optical/mechanical components are self-aligned by the photolithographic process. The DRIE etching depth is 150 μ m, chosen to increase the micromirror optical throughput and improving the out-of-plane stiffness of the MEMS actuator. The MEMS actuator type is closing-gap, while its quality factor is almost doubled by slotting the fixed plate. A low-finesse Fabry–Pérot interferometer is formed by the metallized surface of the micromirror and a cleaved end of a standard single-mode fiber, for characterization of the MEMS actuator stroke and resonance frequency. The actuator achieves a travel distance of 800 nm at a resonance frequency of 89.9 kHz. The notch filter characteristics were measured using an optical spectrum analyzer, and the filter exhibits a free spectral range up to 100 nm and a notch rejection ratio up to 20 dB around a wavelength of 1300 nm. The presented device provides batch processing and low-cost production of the filter.